2010
DOI: 10.1186/1471-2350-11-103
|View full text |Cite
|
Sign up to set email alerts
|

Common variants in the regulative regions of GRIA1 and GRIA3 receptor genes are associated with migraine susceptibility

Abstract: BackgroundGlutamate is the principal excitatory neurotransmitter in the central nervous system which acts by the activation of either ionotropic (AMPA, NMDA and kainate receptors) or G-protein coupled metabotropic receptors. Glutamate is widely accepted to play a major role in the path physiology of migraine as implicated by data from animal and human studies. Genes involved in synthesis, metabolism and regulation of both glutamate and its receptors could be, therefore, considered as potential candidates for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 18 publications
3
46
1
Order By: Relevance
“…The rs3761555 SNP, located at position −1952 C/T in the promoter of the GRIA3 gene, has previously been associated with migraine in the study by Formicola and colleagues in an Italian population . In particular, this study showed association with females and the MWA subtype.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The rs3761555 SNP, located at position −1952 C/T in the promoter of the GRIA3 gene, has previously been associated with migraine in the study by Formicola and colleagues in an Italian population . In particular, this study showed association with females and the MWA subtype.…”
Section: Resultssupporting
confidence: 55%
“…Formicola and colleagues recently analyzed a number of single nucleotide polymorphisms (SNPs) in each of these 4 genes in an Italian population of 250 migraineurs and 260 controls. Their results indicated positive association with 2 SNPs in GRIA1 (rs548294 migraine without aura [MWoA] allelic P = .008, rs2195450 migraine with aura [MWA] allelic P = .0005) and 1 SNP in the GRIA3 promoter (rs3761555 MWA Females allelic P = .003).…”
Section: Introductionmentioning
confidence: 99%
“…GRIA1 and GRIA3 (subunits GluR1 and GluR3) gene polymorphisms are considered potential predisposing/causative factors for migraine. The relationship between the GRIA1 rs548294 and rs2195450 polymorphisms and MA (either as single markers or in haplotype combination) was demonstrated by Formicola et al [39]. This group noted that the rs548294 variant was previously associated with MO.…”
Section: Gene Polymorphisms and Migrainementioning
confidence: 99%
“…However, an association was observed with the GRIA3 polymorphism rs3761555 within the MA subgroup in two independent studies. Moreover, polymorphisms in the regulative regions (rs2195450 GRIA1 and rs3761555 GRIA3 ) modify binding sites of promotors to transcription factors and decrease the expression of these genes [39, 40]. …”
Section: Gene Polymorphisms and Migrainementioning
confidence: 99%
“…The glutamatergic system has not been studied as extensively as that of serotonin and dopamine however the biological constituents including enzymes, glutamate receptors and transporters which mediate excitatory signals via ionotropic and metabotropic receptors have been proposed as candidates to investigate in light of recent genetic studies implicating glutamate in migraine [105-107]. Further research into the glutamatergic system is necessary to confirm its role in migraine susceptibility and pathophysiology.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%